The influence of anti-cancer therapies on lymphocyte subpopulations of lung cancer patients - Gessner, Philipp; Tessema, Belay; Scholz, Markus; Sack, Ulrich; Boldt, Andreas; Kühnapfel, Andreas; Gessner, Christian (Frontiers in Immunology, 2023)
There are limited data on the influence of different anti-cancer therapies on lymphocyte subpopulations and their relationships to survival of non-small cell lung cancer (NSCLC) patients. This study aimed to assess the effect of immunotherapy, chemotherapy, immunochemotherapy, adjuvant chemotherapy after surgery, and antibodies against Vascular Endothelial Growth Factors (VEGF) on B cell, T cell, and NK-cell subpopulations, and the survival time of NSCLC patients. A total of 32 consecutive NSCLC patients were recruited at Pulmonology Clinic, Leipzig from January 2018 to March 2020 and enrolled in this study. Immunophenotyping was done using a FACS Canto II flow cytometer (BD Biosciences) before the administration of the planned therapy and during therapy with up to 7 observational windows for each patient targeting 130 immunologic parameters. Absolute transitional B cells was significantly increased after immunotherapy (p = 0.032), immunochemotherapy (p = 0.030), and antibodies against VEGF (p = 0.024). Similarly, absolute counts and percentage of B cells were significantly increased after adjuvant chemotherapy (p = 0.023). However, absolute counts and percentage of transitional B cells are significantly decreased after chemotherapy (p = 0.001). Activated cytotoxic T cells were significantly increased after immunotherapy (p = 0.031) and immunochemotherapy (p = 0.030). The overall survival rate of NSCLC patients was 31%. In conclusion, this study suggests that different types of anti-cancer therapies affect lymphocyte subpopulations of NSCLC patients. Further large-scale and multicentre studies are required to confirm our results and to evaluate the prognostic value of lymphocyte subpopulations.